Now at last heart is coming back to us” (Tac., Agr., 3, 1): Tacitus and the political-literary dynamics under the Roman Principate - Dias, Mamede Queiroz (Romanitas - Revista de Estudos Grecolatinos, 2023)
This paper analyzes the sociopolitical milieu in the Roman Principate and Tacitus’ exemplary narrative, focusing on the cases of Julius Agricola and Marcus Lepidus. It seeks to emphasize the articulation between the works and the public life of the author. On the one hand, as was customary in Latin prose, Tacitus elaborated and compared exempla of virtuous and vicious men; on the other hand, he sought to remain privileged in a new political context, under Nerva and Trajan, moving away from Domitian, murdered in his own house. Throughout the text, the central hypothesis argues that political and literary communication was constituted through contradictory temporalities, republican and imperial ones, producing ambiguous and paradoxical effects on both the political performance and the literary narrative during the Principates of the 1st and 2nd centuries.
Keywords: Roman Principate; Tacitus; Cursus honorum; Exempla